(untitled) (Medicine Today, 2021)
Introduction: The implementation of the vaccine has already been shown to be a great success to reduce communicable diseases and its associated morbidity among human globally. The aim of this study was to figure out the actual rate of population who received non EPI bacterial and viral vaccines and to determine the risk factors associated with it. Materials and Methods: A retrospective observational study was conducted between September 2011 and August 2014 among 3600 students aged from 18 years to 24 years. Data of total 12 non EPI vaccines (5 bacterial - Cholera and ETEC diarrhea vaccine, Meningococcal, Pneumococcal, Tetanus and Typhoid; 7 viral- Chicken pox, Cervical vaccine, Hepatitis A, Hepatitis B, Measles Mumps Rubella vaccine, Rota viral and Seasonal flu vaccine) were collected from the individuals’ vaccine cards. All vaccine timelines were categorized into timely, early, delayed and missed based on recommended time of vaccination. Different parameters were considered to determine the socio-demographic factors related to vaccination. Results: Total of 3600 study population were selected from three different institutes. Percentage of rural students was almost 3.2 times higher than that of urban. About 1746(48.5%) student were from middle class family. About 2125(59.03%) of the participant’s had not adequate knowledge of vaccination. Out of 3600 study population for bacterial vaccine, rate of Tetanus vaccine was the highest in percentage which was 1248(34.67%). Percentage of other bacterial vaccines such as Cholera and ETEC diarrhea, Meningococcal, Pneumococcal and Typhoid vaccination percentages were only 27(0.75%), 29(0.81%), 111(3.08%) and 34(0.94%) respectively. Among viral vaccines, the highest receiving vaccine was Hepatitis B. 2763(76.75%) people were immune with hepatitis B vaccine. Percentage of Hepatitis A was 337(9.36%), Rota viral vaccine was 330(9.17%), Measles Mumps Rubella was 249(6.92%) and Chicken pox was 83(2.31%). The percentage was less in case of Cervical HPV and Seasonal flu vaccines which were 12(0.33%) and 20(0.56%) respectively. Conclusion: Vaccines have proven the potential capability to reduce vaccine-preventable diseases, however, findings from the study show that people have still not been aware of non EPI bacterial and viral vaccines which can protect people from life threatening diseases and their complications. Medicine Today 2021 Vol.33(1): 80-83